2022
DOI: 10.1007/s00246-022-02961-6
|View full text |Cite
|
Sign up to set email alerts
|

Which Findings Make multisystem Inflammatory Syndrome in Children Different from the Pre-Pandemic Kawasaki Disease?

Abstract: Multisystem Inflammatory Syndrome in Children associated with COVID-19 infection attracted attention because some features overlapped with Kawasaki disease. And due to these overlapping features with Kawasaki disease, it has become difficult to diagnose both disorders. Therefore, this study focused on the differences between the patients diagnosed with MIS-C after COVID-19 and Kawasaki patients analyzed, particularly during the pre-pandemic period. In this way, it is aimed to reduce the dilemmas experienced in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 37 publications
2
6
0
1
Order By: Relevance
“…Additionally, myocarditis is more common and severe in PIMS-TS. Hypoalbuminemia, lymphopenia, and renal insufficiency are also more apparent [6,7]. This clinical case sheds light on hypoalbuminemia as an important feature in PIMS-TS, associated in most cases with the severe evolution of this syndrome [7], which fits with the results of the literature [6,7].…”
Section: Discussionsupporting
confidence: 83%
“…Additionally, myocarditis is more common and severe in PIMS-TS. Hypoalbuminemia, lymphopenia, and renal insufficiency are also more apparent [6,7]. This clinical case sheds light on hypoalbuminemia as an important feature in PIMS-TS, associated in most cases with the severe evolution of this syndrome [7], which fits with the results of the literature [6,7].…”
Section: Discussionsupporting
confidence: 83%
“…This finding is consistent with previous studies. [13][14][15][16] As in the literature, the male gender was dominant in both disease groups, but the difference between the groups was not statistically significant. 13,15,16 It has been reported that mucocutaneous symptoms (conjunctivitis, erythematous/chapped lip), changes in the limbs (desquamation), and cervical LAP were more common in KD patients than in MIS-C patients.…”
Section: Discussionmentioning
confidence: 47%
“…54 In comparison to multisystem inflammatory syndrome, patients with Kawasaki disease are less likely to have lymphopenia but are more likely to have leukocytosis and neutrophilia. [55][56][57][58] In Kawasaki disease, absolute lymphocyte count remains stable in the acute, subacute, and convalescent phase of the disease, and it is rather the lymphocyte percentage that increases after ntravenous immune globulin treatment. 59 Instead of a specific value of either lymphocytes or neutrophils, studies have looked at the neutrophil-to-lymphocyte ratio in Kawasaki disease.…”
Section: Discussionmentioning
confidence: 99%